Optophysiological Approach to Resolve Neuronal Action Potentials with High Spatial and Temporal Resolution in Cultured Neurons - Pages, Stephane; Côté, Daniel; De Koninck, Paul (Frontiers in Cellular Neuroscience, 2011)
Cell to cell communication in the central nervous system is encoded into transient and local membrane potential changes (ΔVm). Deciphering the rules that govern synaptic transmission and plasticity entails to be able to perform Vm recordings throughout the entire neuronal arborization. Classical electrophysiology is, in most cases, not able to do so within small and fragile neuronal subcompartments. Thus, optical techniques based on the use of fluorescent voltage-sensitive dyes (VSDs) have been developed. However, reporting spontaneous or small ΔVm from neuronal ramifications has been challenging, in part due to the limited sensitivity and phototoxicity of VSD-based optical measurements. Here we demonstrate the use of water soluble VSD, ANNINE-6plus, with laser scanning microscopy to optically record ΔVm in cultured neurons. We show that the sensitivity (> 10 % of fluorescence change for 100 mV depolarization) and time response (submillisecond) of the dye allows the robust detection of action potentials (APs) even without averaging, allowing the measurement of spontaneous neuronal firing patterns. In addition, we show that back-propagating APs can be recorded, along distinct dendritic sites and within dendritic spines. Importantly, our approach does not induce any detectable phototoxic effect on cultured neurons. This optophysiological approach provides a simple, minimally invasive and versatile optical method to measure electrical activity in cultured neurons with high temporal (ms) resolution and high spatial (µm) resolution.